Vascular endothelial growth factor in tumor angiogenesis - Łojko, Anna; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2004)
Vascular endothelial growth factor (VEGF), also known as vascular permeability factor (VPF) or vasculotropin, is a key factor in normal and pathological angiogenesis. VEGF is a mitogen for vascular endothelial cells derived from arteries, veins, and the lymphatic system. The formation of the vascular system is essential for tumor growth and metastasis. Increased levels of VEGF in urine, serum, plasma, or malignant tissue have been recorded in many tumor types, including colorectal, gastric, breast, non-small cell lung, prostate, kidney and bladder cancers. VEGF expression is closely correlated with microvessel density and seems to be an important predictor for both liver metastases and poor prognosis in ductal pancreatic cancer. Expression of VEGF in malignant tissue correlates with metastases in patients with colon cancer. An increased plasma VEGF level in patients with non-small cell lung cancer is associated with distant metastasis presence. VEGF is also overexpressed in hematologic malignancies. Increased levels of plasma VEGF have been found in acute myeloid leukemia and myelodysplastic syndromes. In the context of the close relation between tumor and angiogenesis it was suggested that inhibiting angiogenesis would have an antitumor effect. Preclinical models with the use of VEGF inhibitors or monoclonal anti-VEGF antibody are very promising. However, to date, clinical models have not confirmed these results. In the near future the regulation of VEGF expression seems to be the subject matter of many researches.